Guarantees of the inviolability of a witness entitled to protection - Akhpanov, A.N.; Khan, A. L. (Bulletin of the Karaganda University “Law Series”, 2024)
The research purpose of the article is that the authors attempt to solve the problems of establishing the optimal status of participants in the ongoing pre-trial investigation interested in the outcome of the case, whose legal situation was not properly regulated in the current Code of Criminal Procedure of the Republic of Kazakhstan in 2014 and, thereby, gave rise to reasonable difficulties in law enforcement. We are talking about a new subject of the pre-trial stage of the criminal process, attributed to the participants defending their own or represented interests: a witness who has the right to protection, and guarantees of his inviolability. The authors turned to universal and legal methods of scientific research, tools of applied analytics. The achieved results are expressed in the fact that they note the inconsistency and inconsistency of the legislator's introduced innovations aimed at resolving issues of the ratio of private and public principles of legal proceedings in establishing the status of the participant in question, which do not actually change the problems that have arisen, only increasing the bureaucratization of legal proceedings. The proposal of representatives of the General Prosecutor's Office of the Republic of Kazakhstan on the need to increase the repressive approach to a witness who has the right to protection by restricting his freedom of movement is criticized. As a result of the research, the authors conclude that in order to resolve these issues, it is necessary to improve legislation by making amendments and additions to the current version of the norms of the CPC of the Republic of Kazakhstan regulating the procedural status of a witness entitled to protection.